Simulation of rational transfer functions with adjustable coefficients - Paul, R. J. A. (College of Aeronautics, 1962)
Design techniques are described for the simulation of quadratic functions with independent control of each coefficient. Rational function approximations, for the simulation of dead time, are considered. Other typical examples are described and include the simulation of Butterworth functions, Chebyshev functions and orthonormal functions, which have application in self optimizing control systems.